GANGGUAN BERBAHASA PADA PENDERITA CEREBRAL PALSY SEBUAH KAJIAN LINGUISTIK KLINIS - Syahid, Agus (Humanitatis : Journal of Language and Literature, 2020)
This study describes language disorders in the people with cerebral palsy and what kind of treatments to people with cerebral palsy related to language disorders. Cerebral palsy is a series of disorders with problems regulating muscle movements where it is as a result of some damage to the motor centers in the brain. Damage to the motor center in the brain that causes cerebral palsy can occur prenatal (before birth), perinatal (during the birth), or even postnatal (immediately after birth). There are several main problems that are often found and faced by children with cerebral palsy, they are: (1) difficulty in eating and swallowing caused by motor disturbances in the mouth, (2) difficulty in speaking, (3) difficulty in hearing, and (4) language disorders.